Fetal exposure to alcohol and its effects on child neurodevelopment: A literature review (Research, Society and Development, 2024)
Alcohol consumption during pregnancy has been recognized as a global public health issue due to its severe implications for child development. Alcohol is a teratogenic substance that crosses the placenta, directly affecting the Central Nervous System (CNS) of the developing fetus. Studies have linked prenatal alcohol exposure (PAE) to a wide range of impairments, including cognitive, behavioral, and social deficits. In this context, the article aimed to analyze the impacts of PAE on child development, focusing on attention, memory, executive skills, and behavior, as well as exploring aggravating factors. This review utilized databases such as PubMed and SciELO, considering studies published between 2014 and 2024 and applying the PICO strategy criteria. The findings indicated that PAE interferes with essential brain development processes, primarily affecting areas like the hippocampus and prefrontal cortex, which are responsible for cognition and behavior. The severity of the damage was linked to the dose and pattern of alcohol consumption, as well as the nutritional status of the pregnant woman and prenatal care access. The lack of standardized criteria for diagnosing conditions such as fetal alcohol syndrome complicates clinical management and hinders early diagnosis. Therefore, PAE causes multifaceted and long-lasting consequences, highlighting the need for preventive strategies, early diagnosis, and multidisciplinary interventions to mitigate its effects. Furthermore, future studies should prioritize developing innovative therapeutic approaches and effective public policies to reduce the impacts of this exposure on child development.